The role of digital technologies in the innovation of collaborative networks: The case of the ornamental stones in Portugal - Silva, A. M. A. da.; Silva, J. M. V.-B. da; Almeida, I. D. de. (Proceedings of the 20th Cambridge International Manufacturing Symposium - Architecting the digital supply chain: The implications of digitalisation for global manufacturing, 2016)
This exploratory research outlines an innovative business model for the ornamental stones, in Portugal, targeting World Class Manufacturing. Research questions arise from an inductive approach empirically based on a participant-observer that participated in JETSTONE and INOVSTONE, two important Mobilising Projects for the cluster. A collaborative network pursuing a Service Systems view, leveraged by digital technologies was proposed based on a 3-stage development facilitated by the ARCON framework (ECOLEAD project), as follows: development of a general VBE/VO model completed by knowledge coming from BIM, Industry 4.0, IoT and Service Science backgrounds, in order to build up a specific model to the ornamental stones Industry. Finally, the specific model should be verified by case studies as demonstrating instances. While the generic VBE/VO might be customized to other domains, the specific model generates a representation of the Industry and the case studies serve as instances to verify it.